PREPARING FOR FAMILY CREATION AND MARRIAGE AS COMPONENTS OF SEX ROLE SOCIALIZATION, SEXUAL EDUCATION OF CHILDREN AND ADOLESCENTS XX-XXI CENTURIES (Education in the 21st Century, 2023)
The complicated socio-economical situation in Ukrainian society negatively affects the family as the main social institution in which the personality of the future family man is brought up. The following trends are characteristic in the development of the modern Ukrainian family: high rates of divorces; an increase in the number of single-parent families and children born out of wedlock; increase in the average age of people getting married; spreading the idea of voluntary childlessness “child free”; joint couples living without wedlock; an increase in the number of single people who do not marry; reduction in the number of re-marriages.All of the mentioned above directly affects the process of sex-role socialization of children and adolescents, the assimilation of models of the sex-role behavior, the fulfillment of sex-role functions.Scientists considered the preparation of children and adolescents for family life through the organization and implementation of special courses and programs in a school as one of the ways to resolve the situation, such as the introduction of mandatory courses “Hygienic and Sexual Education” in the 8th grade by the decision of the USSR Ministry of Education from 1983 class and "Ethics and Psychology of Family Life" in the 10th grade, the publication of manuals for teachers and students.Nowadays, relevant manuals on preparing children and adolescents for family life, revealing the urgent issues of the process of sex-role socialization, are manuals: “Psychological and pedagogical patterns of preparing pupils for family life”, “Sexual socialization of children and adolescents: patterns and gender characteristics” (В. Kravets); “Ethics and Psychology of Family Relationships” (authors V. Tokas, O. Plyska, Y. Fruktovaya); “Family Values: a practice-oriented manual for the“ Family Values ”curriculum (authors O. Melnik, T. Kravchenko, L. Kanishevskaya, I. Belotserkovets); “Preserving and strengthening the reproductive health of adolescents and youth: the potential of the community” (N. Zimivets); “Preservation the reproductive potential of students” (V. Orzhekhovskaya); “Preparation of high school students for future family life” (G. Harhan).Being the one of the most important components of the sex-role socialization of children and adolescents, preparation for family life can be provided only if a scientifically based system of educational work is created and cooperates with the formation of culturological knowledge of, ethics, psychology, sexology of marriage, and the education of the personal qualities of a future family man, necessarily considering the psycho-sexual aspect.